Therapeutically targeting essential metabolites to improve immunometabolism manipulation after liver transplantation for hepatocellular carcinoma - Zhang, Wenhui; Zhao, Yu; He, Qiang; Lang, Ren (Frontiers in Immunology, 2023)
Hepatocellular carcinoma (HCC) is the most prevalent primary liver malignancy worldwide and is associated with a poor prognosis. Sophisticated molecular mechanisms and biological characteristics need to be explored to gain a better understanding of HCC. The role of metabolites in cancer immunometabolism has been widely recognized as a hallmark of cancer in the tumor microenvironment (TME). Recent studies have focused on metabolites that are derived from carbohydrate, lipid, and protein metabolism, because alterations in these may contribute to HCC progression, ischemia-reperfusion (IR) injury during liver transplantation (LT), and post-LT rejection. Immune cells play a central role in the HCC microenvironment and the duration of IR or rejection. They shape immune responses through metabolite modifications and by engaging in complex crosstalk with tumor cells. A growing number of publications suggest that immune cell functions in the TME are closely linked to metabolic changes. In this review, we summarize recent findings on the primary metabolites in the TME and post-LT metabolism and relate these studies to HCC development, IR injury, and post-LT rejection. Our understanding of aberrant metabolism and metabolite targeting based on regulatory metabolic pathways may provide a novel strategy to enhance immunometabolism manipulation by reprogramming cell metabolism.